Assessment of Geological Heritage Sites and Their Significance for Geotouristic Exploitation: The Case of Lefkas, Meganisi, Kefalonia and Ithaki Islands, Ionian Sea, Greece - Spyrou, Evangelos; Triantaphyllou, Maria V.; Tsourou, Th.; Vassilakis, Emmanuel; Asimakopoulos, Christos; Konsolaki, Aliki; Markakis, Dimitris; Marketou-Galari, Dimitra; Athanasios Skentos (Geosciences, 2022)
Geological heritage or geoheritage refers to the total of geosites, i.e., areas of high geological interest in a given area. Geosites have a high potential of attracting geotourists, thus contributing to the development of the local economy. Assessing sites of geological interest can contribute to their promotion, as well as their preservation and protection. Greece’s geotectonic position in the convergent zone between the African and Eurasian plates has contributed to the existence of a considerable wealth of geosites, with the particularly active geotectonic region of the Ionian Sea characterized as a geoheritage hotspot. The purpose of this study is the selection of several such sites from the islands of Lefkas, Meganisi, Kefalonia and Ithaki and their assessment regarding their scientific, environmental, cultural, economic and aesthetic value. The most representative sites for the individual disciplines of geology (e.g., geomorphology, tectonics, stratigraphy and palaeontology) have been chosen, mapped and assessed, while indicative georoutes are proposed, which could aid the island’s geotouristic promotion to geologist and non-geologist future visitors.